Assessment of Cardiac Toxicity of Manganese Chloride for Cardiovascular Magnetic Resonance - Lamonzie, Elodie; Vaillant, Fanny; Abell, Emma; Charron, Sabine; El Hamrani, Dounia; Quesson, Bruno; Brette, Fabien (Frontiers in Physiology, 2022)
MRI is widely used in cardiology to characterize the structure and function of the heart. Currently, gadolinium-based contrast agents are widely used to improve sensitivity and specificity of diagnostic images. Recently, Manganese, a calcium analogue, has emerged as a complementary contrast agent with the potential to reveal remaining viable cells within altered tissue. Imaging applications may be limited by substantial toxicity of manganese. Indeed, cardiac safety of manganese is not yet comprehensively assessed. In this study we investigated the effect of MnCl2 (1 to 100 µM) on cardiac function. Hemodynamic function was determined ex vivo using an isolated working rat heart preparation. HL-1 cardiac myocytes were used to investigate cell viability (calcein AM) and calcium cycling (CAL-520 AM). Rat ventricular cardiomyocytes were dissociated by enzymatic digestion. Action potentials and calcium currents were recorded using the patch clamp technique. MRI experiments were performed at 1.5T on formalin-fixed rat hearts, previously perfused with MnCl2. MnCl2 perfusion from 1 up to 100 µM in isolated working hearts did not alter left ventricular hemodynamic parameters. Contractility and relaxation index were not altered up to 50 µM MnCl2. In HL-1 cardiac myocytes, incubation with increasing concentrations of MnCl2 did not impact cell viability. The amplitude of the calcium transients were significantly reduced at 50 and 100 µM MnCl2. In freshly isolated ventricular myocytes, action potential duration at 20%, 50% and 90% of repolarization were not modified up to 10 µM of MnCl2. L-type calcium current amplitude was significantly decreased by 50 and 100 µM of MnCl2. MRI on heart perfused with 25 µM and 100 µM of MnCl2 showed a dose dependent decrease in the T1 relaxation time. In conclusion, our results show that low concentrations of MnCl2 (up to 25 µM) can be used as a contrast agent in MRI, without significant impact on cardiac hemodynamic or electrophysiology parameters.